Revealing The Functional Role of Bag-1 in MCF-7 Breast Cancer Cells Through CRISPR-Cas9-Mediated Gene Knockout - Dinler Doğanay, Gizem; ARISAN, ELİF DAMLA; KILBAŞ, PELİN ÖZFİLİZ (My University, 2019)
Bag-1 is a multifunctional protein target which has interactions with a number of cellular proteins. Therefore, Bag-1 participates in several significant biological processes such as cell proliferation, survival, and apoptosis. Elevated expression levels of Bag-1 arc associated with progression o f cancer and resistance mechanism against cancer. In our previous studies, we obtained results showing Bag-1 silencing enhancing the apoptotic potentials of cisplatin or paclitaxel through modulating PI3K/Akt/mT0R pathways in breast cancer cells, however, the function of Bag-1 knockout in these cells has not been fully explored. Here, we performed the CRISPR/Cas9 technique to knockout Bag-1 gene and successfully produced Bag-1 knockout cell line (Bag-1 KO). Sanger sequencing was used to confirm the gene knockout mediated insertions or deletions (indels) in MCF-7 cells. Correspondingly, the mRNA and protein expressions of Bag-1 were markedly reduced. We determined the effect o f Bag-1 KO on cell survival by M il and trypan blue dye exclusion assay. Alternations of total protein expression profiles between wild-type and Bag-1 KO cells were determined through pathscan analysis and immunoblotting assays. Our results showed that knockout of Bag-1 suppressed the proliferation and growth potential of MCF-7 cells by decreasing the number of colony formations. According to the immunoblotting results, knockout of Bag-1 significantly upregulated Akt phosphorylation and b-actin downregulation. We concluded that Bag-I inlluenced actin disorganization through stress-induced Akt activation and alternations on expression profiles o f focal adhesion kinases.